History and Speculative Fiction - Hennessey, John L. (Springer Nature, 2024)
This open access book demonstrates that despite different epistemological starting points, history and speculative fiction perform similar work in "making the strange familiar" and "making the familiar strange" by taking their readers on journeys through space and time. Excellent history, like excellent speculative fiction, should cause readers to reconsider crucial aspects of their society that they normally overlook or lead them to reflect on radically different forms of social organization. Drawing on Gunlög Fur's postcolonial concept of concurrences, and with contributions that explore diverse examples of speculative fiction and historical encounters using a variety of disciplinary approaches, this volume provides new perspectives on colonialism, ecological destruction, the nature of humanity, and how to envision a better future.